Development of E-Comic Media to Improve Critical Thinking Skills in Addition Material in Grade IV Elementary School - Astuti, Berliana Puji; Kowiyah , Kowiyah (FKIP - Universitas Riau, 2025)
The development of learning media enhances students' critical thinking skills, especially in elementary mathematics. This research produced an interactive E-Comic focusing on addition material for fourth-grade students, following the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validation by media experts, material experts, language experts, and education practitioners showed high feasibility with an average score of 92%. Small group trials with 6 students yielded 92%, while larger group testing with 32 students achieved 97%. Pre-test and post-test results demonstrated significant improvement, increasing from 44.06% to 83.98%. These findings prove the E-Comic's effectiveness in improving learning outcomes and fostering critical thinking skills. The engaging visuals and interactive presentation motivate students, making mathematics learning more enjoyable and meaningful. Therefore, the E-Comic proves to be an effective learning medium for enhancing both students' critical thinking abilities and achievement in addition material. The ADDIE model ensured systematic development and proper validation standards were maintained throughout the research process, resulting in a highly effective educational tool.